The Mediating Role of Emotional Intelligence in Predicting of Self â€“ Efficacy in Mathematical Thinking among Fourth Grade Students in the Sultanate of Oman - Al-Kiyumi, Mohammed; Alfalasi, Amina (Mediterranean Journal of Social Sciences, 2021)
This study aimed to investigate the role of emotional intelligence in predicting self-efficacy in mathematical thinking. The sample consisted of 150 students selected by cluster and sample random techniques from Al-Buraimi governorate. The tools of the study were: Mathematical Thinking Scale developed by the researchers, Self-efficacy Scale for Children (SEQ-C), and Bar-On Emotional Intelligence scale. The results showed a statistically significant correlation between mathematical thinking, self-efficacy, and emotional intelligence. The self-efficacy predicted mathematical thinking when emotional intelligence was a mediator. The variables of sex and the type of school had an impact on the prediction of mathematical thinking. Based on the results, the researchers recommended attention to the development of psychological factors that contribute to the development of mathematical thinking, including self-efficacy and emotional intelligence. They also recommended that further studies be carried out to investigate the role of different psychological traits in mathematical thinking.Contribution/Originality: this study is one of very few studies that investigated to how much extent that self-efficacy predicts mathematical thinking when emotional intelligence plays a mediating role. This investigation was conducted in a new environment. Â  Received: 10 June 2021 / Accepted: 10 August 2021 / Published: 5 September 2021